Innovate to Lead or Innovate to Prevail : When do Monopolistic Rents Induce Growth? - Piazza, Roberto (IMF Working Papers; Working Paper ;, 2019)
This paper extends the Schumpeterian model of creative destruction by allowing followers' cost of innovation to increase in their technological distance from the leader. This assumption is motivated by the observation the more technologically ad- vanced the leader is, the harder it is for a follower to leapfrog without incurring extra cost for using leader's patented knowledge. Under this R and D cost structure, leaders innovate to increase their technological advantage so that followers will eventually stop innovating, allowing leadership to prevail. A new steady state then emerges featuring both leaders and followers innovating in few industries with low aggregate growth.